The Global Refugee Crisis: Empirical Evidence and Policy Implications for Improving Public Attitudes and Facilitating Refugee Resettlement. Issue 1 (January 2017) - Esses, Victoria M.; Hamilton, Leah K.; Gaucher, Danielle
Abstract : The number of refugees across the globe is at an alarming high and is expected to continue to rise for the foreseeable future. As a result, finding durable solutions for refugees has become a major challenge worldwide. The literature reviewed and policy implications discussed in this article are based on the premise that one of the major solutions to the refugee crisis must be refugee resettlement in new host countries. For such a solution to succeed, however, requires relatively favorable attitudes by members of host societies, protection of the well‐being of refugees, and effective integration of refugees into new host countries. In this context, we begin by reviewing the literature on determinants of public attitudes toward refugees, the acculturation of refugees in host societies, and factors affecting refugee mental health, all of which are directly relevant to the success of the resettlement process. We then turn our attention to the policy implications of these literatures, and discuss strategies for improving public attitudes toward refugees and refugee resettlement in host countries; for improving the resettlement process to reduce mental health challenges; and for supporting the long‐term acculturation and integration of refugees in their new homes.